An integrated method for wind power estimation: Application for coastal areas in cyprus - Kastanas, Ioannis; Georgiou, Andreas G.; Zavros, Panagiotis; Pashiardes, Stelios; Akylas, Evangelos (My University, 2013)
In this study, the framework of an integrated method for the estimation and analysis of potential wind energy resources in Cyprus is presented and applied, at three selected sites at the western coast-line of the island. Firstly, a statistical analysis of wind speed and direction data for selected meteorological stations at the Cyprus coast is carried out. Daily, monthly and annual variations of wind speed are established. The Weibull distributions of the sites are also determined and examined. The wind statistics obtained serve as the basis in order to estimate corrected statistical distributions over the extended areas of application through Wind Atlas Analysis and Application Program (WAsP) which modifies the wind flow due to local topographic effects. As a result, a geo-data and wind resource base is formulated around each station. Aggregation of the data with statistical weighting methods, allows the extrapolation of the results and the visualization over the western part of the island. The application indicates the strong influence of the sea-breeze on the wind potential of the island and recovers interesting points with higher wind energy potential, suitable for wind resource exploitation. The particular methodological framework applied and the results obtained can be utilized by potential investors and wind energy developers.
Keywords: Cyprus coast; WAsP; Weibull; Wind energy